Effect of edge plasma density on hot spot in LHCD plasma in EAST. (June 2021) - Ding, B.J.; Wu, C.B.; Li, Y.C.; Li, M.H.; Wang, Y.F.; Zhang, B.; Yan, G.H.; Liu, H.Q.; Wang, L.; Wang, M.; Ding, R.; Hu, H.C.; et al.
Highlights: Investigating effect of edge density and LH power on hot spot and current drive. Hot spot is mainly ascribed to the heat flux in front of LH antenna. Due to PI behavior, current drive capability decreases with edge density, in consistent with strike-point splitting behavior and current profiles in edge region. Offering one possible idea to optimizing the edge density so as to satisfy the coupling, mitigate the heat flux in the guard limiter, and improve current drive capability for fusion device. Abstract: Hot spot is a serious challenge limiting long pulse operation with LHCD (lower hybrid current drive) in tokamak. In order to mitigate the hot spot in guard limiter and improve LHCD capability, effect of edge plasma density on inducing hot spot and current drive has been studied in EAST. The temperature in the guard limiter of the LH antenna, inducing hot spot directly, increases with edge density and LH power. Studies show that the hot spot is mainly ascribed to the heat flux in front of LH antenna. Further simulation indicates that such spot corresponds to the peak position of edge density due to local LH electric field. In addition, due to the stronger parametric instability (PI) behavior in the case of higher edge density, the current drive capability decreases with edge density. Strike-point splitting behaviors appear with density increase, in agreement with current profiles in the edge region and the reduction of total driven current, suggesting that more power is deposited in edge region, which does more contribution to hot spot. Above studies offer one possible idea to optimize the edge density so as to satisfy the coupling, mitigate the heat flux in the guard limiter, and improve current drive capability for fusion device.